Влияние легирования вольфрамом на структуру и механические свойста никелида титана - Турская, Виктория Сергеевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
In this work, a study was made of an alloy for medical purposes based on nickel titanium alloyed with tungsten. The phase composition was established by X-ray diffraction analysis, and the elemental composition of the microstructure was studied. It has been established that W is present in the TiNi alloy in the form of separate particles, the average size of which is 0.5 μm. Alloying TiNi alloys with tungsten shifts the direct martensitic transformation (MT) towards lower temperatures. The dependence of stress on strain already at СW=0.4 at. % in the TiNi alloy does not have the traditional plateau associated with the formation of stress martensite, presumably due to a decrease in the volume fraction of the B2 phase by 50%. The practical application of TiNiW alloys is promising at a W concentration of up to 0.2 at. %.